Cost impact in implementing green materials in Malaysia's housing construction / Nur Nabila Suhada Mohd Noh and Dr Suhaila Ali - Mohd Noh, Nur Nabila Suhada; Ali, Suhaila (2020)
The concept of green housing incorporates and integrates various strategies in the design, construction and operation of the building project. The use of green building materials and products represents an important strategy in house design. The use of green building materials and products can promote the protection of dwindling non-renewable resources. In addition, integrating green building materials into housing projects can help reduce the environmental impact associated with the extraction, transportation, processing, manufacturing, installation, reuse, recycling, and disposal of these industrial sources materials. However, costs have always been the biggest problem for green housing growth. This causes other problems such as less attractive to investors due to high prices compared to others. In addition, the expectation that green housing prices are higher than conventional housing has made it more difficult to implementation of green materials. Therefore, it is important to understand the underlying aspects that affect greenhouse prices. At the same time researching the things that make green materials more beneficial to green housing, even where costs have increased. The results of this study show the cost impact on the uses of green materials in the construction of green housing from the perspective of the developer. Based on the findings obtained from this study most developers agree that green housing is more expensive than conventional housing. However, they do not deny that green housing is also beneficial because green housing will save on utility bills for owners or household through energy and water efficiency. The finding suggests a ground for the next level of study to further explore how these considerations affect the cost and decision-making of the project.